Hábitos alimentarios en pacientes con diabetes tipo II en la parroquia Santa Fe provincia Bolívar durante período agosto 2016-enero 2017 - Monar Acurio, Esthela Lourdes (2017)
The present study was carried out with the users diagnosed with diabetes mellitus type II who attend the Santa Fe Health Center, whose objective was to reduce the incidence and prevalence of inadequate eating habits, and then contribute to educational talks that guarantee a Healthy eating of diabetics. In this investigative work we used the analytical methodological design that allowed us to get to know the existing problems with patients diabetes mellitus type II and to make known about the correct form of feeding, since with this work was related to the 40 people Who did not provide information on their eating habits. For data collection, clinical records were reviewed at the Santa Fe Health Center and the patients with type II diabetes mellitus were surveyed. This technique was able to identify the inadequate diet they maintain. Most diabetics have an adequate diet which is 65%, while 35% have an inadequate diet that has an impact on their health status. To do this, it is necessary to raise the awareness of users with diabetes through educational talks about proper nutrition, since these people should eat vegetables, carbohydrates in low portions, white meat, reduce sugar levels, perform physical exercise and guide the intake of medications to Its due schedule.